Effective Classroom Management in English as a Foreign Language Classroom - Burhanuddin Yasin; Faisal Mustafa; Ayu Mentari Sarani Bina (Master Program in Linguistics, Diponegoro University, 2022)
Classroom management is an essential element of the teaching and learning process which determines the quality of instruction. This research aims to investigate the elements of classroom management which can be effectively applied in EFL classrooms. This study is a review research study, where the data were collected from 43 previously published materials, restricted to books, dissertations, and articles published in academic journal. The data were analysed using data condensation, data display and conclusion drawing. The results of this study show that there are three elements of classroom management, i.e. seating arrangements, engagement, and participation. The seating arrangement has three effective components including u-shaped, sitting in a group, and orderly row. Further, student engagement consists of cognitive, behavioural, academic, emotional, social, intellectual, physiological, affective and relational engagement approaches. Meanwhile, participation includes classroom talk, teacher talk, collaborative talk, exploratory talk, disputational talk, and learner-managed talk. Therefore, it is recommended that teachers utilize effective classroom management components based on the results of this study to improve the quality of instruction.